1996
DOI: 10.2307/1592222
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Infectious and Parasitic Diseases in Poultry Slaughtered in the District of Olsztyn, Poland, 1986-91

Abstract: During 6 years, 1986-91, in poultry processing plants in the district of Olsztyn, Poland, 37,779,959 carcasses and internal organs of slaughtered fattened poultry were (1,691,188 hens, 23,681,855 chickens, and 12,226,016 turkeys) were examined. As a result of the antemortem and postmortem inspections, 744,499 birds were condemned for human consumption, which was 1.66% of the total number of birds examined. The highest percentage of condemned birds was registered in hens (2.4%) and the lowest in chickens (1.27%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
9
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 3 publications
4
9
0
1
Order By: Relevance
“…Similarly to other research the incidence of avian leukosis (AL) among all birds (up to 2%) was low and also less frequently noted than MD (Balachandran et al 2009); however, in some reports AL was even more rare (Radkowski et al 1996). In our own study, the mean age of layers was in agreement with an earlier report (Balachandran et al 2009).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similarly to other research the incidence of avian leukosis (AL) among all birds (up to 2%) was low and also less frequently noted than MD (Balachandran et al 2009); however, in some reports AL was even more rare (Radkowski et al 1996). In our own study, the mean age of layers was in agreement with an earlier report (Balachandran et al 2009).…”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to findings obtained in other studies, where peripheral nerve infiltration was observed only in layers (2.8%) (Wieliczko et al 2002). In another retrospective study MD was noted less frequently (0.1%) in chickens from the north-east of Poland (Radkowski et al 1996). Interestingly, our results were similar to those (3.03%) obtained in a histopathological survey conducted on other continent (Balachandran et al 2009).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Septicemia, also known as toxemia, is a general condemnation category that includes clear signs of systemic disease involvesecond common reason was cachexia (25.7%). A survey of poultry carcass condemnation was carried out in Poland, 1986Poland, -1991 carcasses were examined and 1.66% was condemned and the most common reason for condemnation was Marek's disease (Radkowski et al, 1996). In England and Wales, 1992-1993, 1.3% of slaughtered broilers were condemned and septicemia/toxaemia/fever was the most common causes of condemnation (Bremner, 1994).…”
Section: Discussionmentioning
confidence: 99%